Retrospective Clinical Evaluation of a Decision-Support Software for Adaptive Radiotherapy of Head and Neck Cancer Patients - Gros, Sebastien A. A.; Santhanam, Anand P.; Block, Alec M.; Emami, Bahman; Lee, Brian H.; Joyce, Cara (Frontiers in Oncology, 2022)
Purpose: To evaluate the clinical need for an automated decision-support software platform for Adaptive Radiation Therapy (ART) of Head-and-Neck cancer (HNC) patients. Methods: We tested RTapp (SegAna), a new ART software platform for deciding when a treatment replan is needed, to investigate a set of 27 HNC patients’ data retrospectively. For each fraction, the software estimated key components of ART such as daily dose distribution, and cumulative doses received by targets and OARs from daily 3D imaging in real-time. RTapp also included a prediction algorithm that analyzed dosimetric parameters (DP) trends against user-specified thresholds to proactively trigger adaptive replanning up to 4 fractions ahead. The DPs evaluated for ART were based on treatment planning dose constraints. Warning (V95<95%) and adaptation (V95<93%) thresholds were set for PTVs, while OAR adaptation dosimetric endpoints of +10% (DE10) were set for all Dmax and Dmean DPs. Any threshold violation at end of treatment (EOT) triggered a review of the DP trends to determine the threshold-crossing fraction Fx when the violations occurred. The prediction model accuracy was determined as the difference between calculated and predicted DP values with 95% confidence intervals (CI95). Results: RTapp was able to address the needs of treatment adaptation. Specifically, we identified 18/27 studies (67%) for violating PTV coverage or parotids Dmean at EOT. Twelve PTVs had V95<95% (mean coverage decrease of -6.8 ±2.9%) including 6 flagged for adaptation at median Fx= 6 (range: 1-16). Seventeen parotids were flagged for exceeding Dmean dose constraints with a median increase of +2.60 Gy (range: 0.99-6.31 Gy) at EOT, including 9 with DP>DE10. The differences between predicted and calculated PTV V95 and parotids Dmean was up to 7.6% (mean±CI95: -2.7±4.1%) and 5 Gy (mean±CI95: 0.3±1.6 Gy), respectively. The most accurate predictions were obtained closest to the threshold-crossing fraction. For parotids, the results showed that Fx ranged between fractions 1 to 23, with a lack of specific trend demonstrating that the need for treatment adaptation may be verified for every fraction. Conclusion: Integrated in an ART clinical workflow, RTapp aids in predicting whether specific treatment would require adaptation up to four fractions ahead of time.